SIFAT KEIBUAN DALAM DUA CERITA PENDEK THE SHAWL DAN TWO KINDS - LUDONG, LUISIANI DEBORA JELLY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
Abstract The research is entitled Motherhood in the Two Short Stories The Shawl and Two Kinds. The objective of this research is to identify, classify, and analyze the motherhood theme as the main theme in the two short stories The Shawl and Two Kinds. The objective of this research is also to compare the reflection of motherhood in these both short stories. The writer conducted this research by using descriptive method. The data were collected by focusing on the character, plot, setting, symbol and atmosphere as the elements of prose which reveal the motherhood theme. In analyzing the data, the writer used theory of Stanton (1965) as the main theory and Perrine (1970) and Wellek and Warren (1949) as the supporting theories. The writer also used Kartono’s (2007) idea to identify the motherhood in the whole sequences of the story. The result of this research shows that these short stories reflect the motherhood portrayed by the intrinsic elements such as character, plot, setting, symbol and atmosphere of the short stories. Both of these short stories have similarities in terms of the reflection of motherhood. The similarities are both characters of mother in the two short stories The Shawl and Two Kinds show their love through the softness, sacrifice, patience, and looking forward for the future. Keywords : Motherhood, The Shawl, Two Kinds, Descriptive Analysis.